2011
DOI: 10.1021/ja2089734
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Proton Transfer Is Not Involved in the Ultrafast Deactivation of Guanine–Cytosine Pair in Solution

Abstract: Different derivatives of Guanine (G) and Cytosine (C), which sterically enforce the Watson-Crick (WC) conformer, have been studied in CHCl(3) by means of broad-band transient absorption spectroscopy. Our experiments rule out the involvement of an Excited State Proton Transfer (ESPT), which dominates the excited state decay of GC in the gas phase. Instead, the ultrafast dynamics via internal conversion occurs in a polar environment mainly by relaxation in the monomer moieties. Time-dependent density functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 23 publications
5
45
0
Order By: Relevance
“…In solution with polar solvents, the SDHT mechanism is presumably altered inactivating the internal conversion channel which brings the WC GC base pair back to its ground state equilibrium structure or to new tautomeric configurations. 96 However, the DNA-embedded GC dimer studied by the QM/MM computational approach manifests the same qualitative behavior for the double proton/hydrogen-transfer processes as in vacuo. This supports experimental observations 86,90,91 and previous theoretical predictions 85,93 pointing out to the proton/hydrogen-transfer as a relevant process in the photochemistry of DNA duplexes.…”
Section: Summary and Concluding Remarksmentioning
confidence: 86%
See 1 more Smart Citation
“…In solution with polar solvents, the SDHT mechanism is presumably altered inactivating the internal conversion channel which brings the WC GC base pair back to its ground state equilibrium structure or to new tautomeric configurations. 96 However, the DNA-embedded GC dimer studied by the QM/MM computational approach manifests the same qualitative behavior for the double proton/hydrogen-transfer processes as in vacuo. This supports experimental observations 86,90,91 and previous theoretical predictions 85,93 pointing out to the proton/hydrogen-transfer as a relevant process in the photochemistry of DNA duplexes.…”
Section: Summary and Concluding Remarksmentioning
confidence: 86%
“…89 In this line, a combined experimental and time-dependent density functional theory (TD-DFT) study on the GC base pair in solution with CHCl 3 has also pointed out to a non-efficient process in solution. 96 The authors of this work have also suggested that the photoinduced hydrogen transfer cannot be considered as a relevant deactivation path in DNA. However, the most recent experiments from de La Harpe et al have reported pronounced isotope effects on the long-lived exciplex excited states of a d(GC) 9 ·d(GC) 9 double-strand, 91 in agreement with independent studies by Doorley et al 90 In this scenario, a model based on the fully characterization of the energy-decay channels involving proton/hydrogen transfer in the GC base pair seems timely in order to establish the operative mechanisms for photostability and tautomerism and to shed some light into the relevance of basepairing in the photodynamics of DNA.…”
Section: Introductionmentioning
confidence: 87%
“…[11][12][13][14][15] In spectroscopic experiments, the effect of hydrogen bonding on the excited-state lifetime of the base pairs has been of great interest. [16][17][18][19][20][21][22][23][24][25][26] In the present work, excited-state potential energy profiles of the Watson-Crick form of the guaninecytosine (GC) base pair are theoretically studied for all of the potentially competing reactions mentioned above: SPT and DPT between guanine (G) and cytosine (C) as well as nonradiative decay in each single base under hydrogen bonding. One purpose of this study is to assess the favorability of the decay process in the G monomer with hydrogen-bonded to C, which was rarely discussed in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…TD-DFT calculations also indicate that even a weakly polar solvent can dramatically alter the energetics of the relevant excited states, leading to a barrier to PT not seen in the gas-phase calculations [178]. Significantly, long-lived excited states with lifetimes of~20 ps are readily observed in a variety of duplexes formed from GC base pairs [180].…”
Section: Single Base Pairsmentioning
confidence: 98%
“…More recent experiments on single base pairs in chloroform have revealed dynamics resembling those of a monomer and failed to document ultrafast PT [70,178,179]. TD-DFT calculations also indicate that even a weakly polar solvent can dramatically alter the energetics of the relevant excited states, leading to a barrier to PT not seen in the gas-phase calculations [178].…”
Section: Single Base Pairsmentioning
confidence: 99%